A case study on the effect of training towards the level of customer service in to fashion retailing chain stores - Kok, Fook Meng (2015)
"The customer is always right" - a premise or philosophy which guides many service organisations. Many organisations believe in this phrase as customers are the life-line to the success of any business. The point of contact between the customers and frontline employees, often known as the service delivery process, greatly determines the number of repeat visits and thus, the continued success of an organisation. The calibre of an organisation's human resources and pool of satisfied customers is vital to this success. The purpose of this study is therefore to understand how and why training is crucial to the delivery of good customer service by frontline employees in the fashion retailing industry with respect to Company A and Company B. To determine the definition of "good" customer service, this study will identify the core and peripheral factors that influence the quality of service delivered by frontline employees in the two case study organisations. Core factors are those variables that the frontline employee himself must possess, while peripheral factors are those variables that the company must possess and provide. A theoretical framework will be presented to establish a general model of the impact of training on the various factors that contribute to good customer service. This paper will present some findings of an empirical study of two "successful" fashion outlets known for good customer service. Open-ended interviews and surveys were conducted with the employers and employees of the two case study organizations concerned. Further field research was conducted to elicit valuable information from the customers of these two organizations. Finally, the paper will present a discussion of the practical implications of the model for organizations attempting to implement successful training towards good customer service. Even though Company A has won awards for providing good and unique customer service, the results of our interviews with both companies' management and staff indicate an emphasis on certain core and peripheral factors contributing to customer satisfaction. Further evaluation into the interviews revealed that the core and peripheral factors were attained through the influence of certain moderating variables.